A new species of the Hypostomus cochliodongroup (Siluriformes: Loricariidae) from the rio Aripuanã basin in Brazil - Zawadzki,Cláudio H. (2014)
A new species of Hypostomus, H. dardanelos, is described from the rio Aripuanã basin, a southern tributary to the rio Madeira, in northern Mato Grosso State, Brazil. The new species is assigned to the Hypostomus cochliodon group by the possession of few teeth, spoon-shaped teeth, angle between dentaries usually less than 80°, and by the absence of a notch between hyomandibular and the metapterygoid. The new species can be diagnosed from its congeners by its unique color pattern of yellowish-brown ground color covered by well-defined dark spots of relatively equal size, evenly spaced and moderately set along the dorsal region of the body and fins, except on the ventrolateral region of the caudal peduncle and proximal region of anal and caudal fins, which are devoid of spots. The new species is further diagnosed by having teeth with very small lateral cusp, fused to the mesial one and almost imperceptible; by the absence of medial buccal papillae, and by nuptial odontodes all along the body (odontodes more pronounced in some few larger specimens).